Laskar Covid-19 Wujudkan Desa Kuanheun Sehat Bebas Covid - Florentianus Tat; Mariana Oni Betan; Aben B.Y.H Romana; Emiliandry Banase (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
The COVID-19 pandemic is still endemic and continues to increase due to rapid transmission. East Nusa Tenggara (NTT) Province, Kupang Regency, West Kupang District, and Kuanheun Village are also areas that have experienced the impact. COVID-19 data in NTT as of May - June 2021 in the age range of 6-18 years has been confirmed as many as 2229 and 350 suspected cases. Objective: to form a group of youth soldiers for COVID-19 in Kuanheun Village. Methods: The training begins with a pre-test and post-test for 30 youth cadres, then the material is given using the lecture method, discussion, and the making of counseling media by teenagers. Increased knowledge of adolescents before training in the good category (23.3%), after training increased to (53.3%), adolescents were trained on how to use spraying equipment, manufacture disinfectants, and manufacture health promotion media prepared by youth with language and culture local. Conclusion: There was a change in adolescent knowledge about COVID-19 prevention, the formation of an organizational structure for the COVID-19 lascar with a work plan related to the COVID-19 prevention promotion program in Kuanheun Village. Suggestion: For Kuanheun village youth to play an active role in implementing the COVID-19 prevention promotion program in Kuanheun Village. Educational institutions continue to make Kuanheun village a partner village, so that community service activities can continue. For the head of Kuanheun village, it is necessary to educate other youths who are not fully involved in youth activities in Kuanheun village. ABSTRAK Pandemi COVID-19 masih mewabah dan terus meningkat karena penularan yang cepat. Provinsi Nusa Tenggara Timur (NTT), Kabupaten Kupang Kecamatan Kupang Barat Desa Kuanheun juga menjadi wilayah yang mengalami dampaknya. Data COVID-19 di NTT per Mei - Juni 2021 pada rentang usia 6-18 tahun terkonfirmasi sebanyak 2229 dan suspek sebanyak 350 kasus. Tujuan: terbentuk kelompok remaja laskar COVID- 19 di Desa Kuanheun. Metode: Pelatihan diawali  pre test dan post test bagi kader remaja berjumlah 30 orang, selanjutnya  pemberian materi dengan metode ceramah, diskusi dan pembuatan media penyuluhan oleh remaja. Peningkatan pengetahuan remaja sebelum dilakukan pelatihan pada kategori baik (23,3%), sesudah pelatihan meningkat menjadi (53,3%), remaja dilatih cara pengunaan alat penyemprotan, pembuatan desinfektan, dan pembuatan media promosi kesehatan yang disusun oleh remaja dengan bahasa dan budaya setempat. Kesimpulan: Terjadi perubahan pengetahuan remaja tentang pencegahan COVID-19, terbentuknya struktur organisasi lascar COVID-19 dengan rencana kerja terkait program promosi pencegahan COVID-19 di Desa Kuanheun. Saran: Bagi remaja desa Kuanheun agar berperan aktif dalm melaksanakan program promosi pencegahan COVID-19 di Desa Kuanheun. Bagi Institusi pendidikan tetap menjadikan desa Kuanheun sebagai desa mitra, agar kegiatan pengabdian masyarakat dapat berlanjut. Bagi kepala desa Kuanheun perlunya edukasi remaja lain yang belum terlibat penuh dalam kegiatan remaja di desa Kuanheun.